MEMPERLUAS KEMAMPUAN ALAT PENCABUT SINGKONG: PENGEMBANGAN LEBIH LANJUT UNTUK KEBUTUHAN PETANI - Sundari, Susanti; Pratama, Aam Wahyu; Suharto; Hidayat, Ghapur (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
This research builds upon the author's earlier work on the design of a cassava pulling tool. The aim is to develop a non-mechanical or minimally-powered tool that addresses farmer needs. The tool design incorporates Quality Function Deployment (QFD) to ensure user satisfaction. QFD is a method that integrates customer desires into technical requirements during the design phase, prior to production. Data analysis revealed key user desires: lightweight materials, affordability, the ability to pull multiple cassava stems simultaneously, durability, safety, and additional functionalities. House of Quality (HOQ) analysis identified the most crucial attribute (weight of importance: 30%) as the ability to pull multiple stems at once. This finding served as the primary basis for prototype development and technical characteristic definition. Subsequent prototype testing successfully uprooted cassava plants, demonstrating the tool's capability of pulling multiple stems in a single operation.